Route Warning System for Monitoring and Accident Prevention in Road Transport - Anjelina, Deby Triana; Humami, Faris; Tsani, Mokhammad Rifqi (ASTONJADRO, 2025)
Accidents in special vehicles transporting B3 are accidents with a higher risk compared to accidents in ordinary vehicles. Based on the news of accidents involving fuel tankers in Candisari Semarang and Karangpucung Cilacap, the accidents that occurred were caused by drivers who were not ready to face changes in the type of road contour. Therefore, additional features are needed on tank cars that can provide delivery route mapping and provide notifications (risk journey) when passing through accident-prone areas. By applying the fuzzy c-means method, route safety identification can be carried out through data grouping based on traffic condition factors as well as accident data. The results of this study are in the form of a route warning application that can detect accident-prone points and provide notifications at a distance of 600 meters before the vulnerable point. This application provides notifications at 20 points on the delivery route to PT Anugerah Makmur Sejahtera. This application can be monitored by the company using web monitoring that is integrated with the route warning application in real time. After going through three tests, this application is feasible to use for adding safety features to tank cars.